anonymous
  • anonymous
@AriPotta
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
is the second one C?
AriPotta
  • AriPotta
1 Attachment

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Question 7: A \[(8+\sqrt{2})(4-3\sqrt{2}) \rightarrow 32 -24\sqrt{2}+4\sqrt{2}-3\sqrt{2}\sqrt{2}\]\[32-20\sqrt{2}-3(2) \rightarrow 32-6-20\sqrt{2} \rightarrow 26-20\sqrt{2}\]
anonymous
  • anonymous
thanks guys!
AriPotta
  • AriPotta
and with the first one, just multiply the two fractions. 2/3 x 4/5 = 8/15
anonymous
  • anonymous
what about the #6 ?
anonymous
  • anonymous
Which of the following is a solution to √x-4+9=6
anonymous
  • anonymous
x = 17 x = 15 x = 5 x = 3
anonymous
  • anonymous
@AriPotta
AriPotta
  • AriPotta
is that sqrt(x - 4) + 9 = 6?
anonymous
  • anonymous
x = –3 x = –7 x = 1 x = 13 I put the wrong answer choices
anonymous
  • anonymous
yes
AriPotta
  • AriPotta
ok, so subtract 9 first
anonymous
  • anonymous
√x-4-3 ?
AriPotta
  • AriPotta
sqrt(x - 4) + 9 = 6 sqrt(x - 4) = -3 then square it [sqrt(x - 4)]^2 = -3^2 x - 4 = 9 add 4 x = 13
anonymous
  • anonymous
i have one more. I gonna see if I can do it
anonymous
  • anonymous
6√x+1=24
anonymous
  • anonymous
I got it wrong. i got 88
anonymous
  • anonymous
x = 17 x = 15 x = 5 x = 3
AriPotta
  • AriPotta
divide by 6 6sqrt(x + 1) = 24 sqrt(x + 1) = 4 square it [sqrt(x + 1)]^2 = 4^2 x + 1 = 16 subtract 1 x + 1 = 16 x = 15
anonymous
  • anonymous
1 Attachment

Looking for something else?

Not the answer you are looking for? Search for more explanations.